Penerapan Model Kirkpatrick Dalam Mengevaluasi Pelaksanaan Diklat Penguatan Kepala Sekolah Melalui Daring Dari Perspektif Pengajar - Rochaendi, Endi; Wahyudi, Andi; Arifin, Ahmad Syamsul; Salim, Ahmad (Literasi: Jurnal Ilmu Pendidikan, 2021)
This study aims to determine the extent to which the implementation of online PKS training is successful. His study used an evaluation with Kirkpatrick's model approach to measure aspects of reaction, learning, behavior and results. As a result, 91.65 percent of training participants showed a high positive reaction to the implementation of the training, and all participants showed behavioral changes in attitudes and actions when carrying out the task of managing the learning and education process in schools. In addition, using non-parametric Mann-Whitney analysis, it can be concluded that there has been an increase in the knowledge of PKS training participants on the aspects of managerial abilities, entrepreneurial development and supervisory skills. The results of the study explained that all training participants passed the training with very satisfying results. Thus, the online mode PKS training has been implemented and resulted in strengthening the capacity of school principals in various required competencies. It is recommended, for the next implementation, it should focus on using pedagogical flexibility to produce a profile of school principals who have a professional vitality construction.Keywords: Capacity Building, Kirkpatrick Model and PKS Training.